Improved systolic ventricular function with normal myocardial mechanics in compensated cardiac hypertrophy - Okoshi, Katashi [UNESP]; Okoshi, Marina Politi [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Gonçalves, Giancarlo [UNESP]; Barros, Reginaldo [UNESP]; Cicogna, Antonio Carlos [UNESP] (International Heart Journal (Japanese Heart Journal), 2002)
There still controversy about the relation between changes in myocardial contractile function and global left ventricular (LV) performance during stable concentric hypertrophy. To clarify this, we analyzed LV function in vivo and myocardial mechanics in vitro in rats with pressure overload-induced cardiac hypertrophy. Male Wistar rats (70 g) underwent ascending aorta stenosis for 8 weeks (group AAS, n=9). LV performance was assessed by transthoracic echocardiography under light anesthesia. Myocardial function was studied in isolated papillary muscle preparation during isometric contraction. The data were compared with age- and sex-matched sham-operated rats (group C, n=9). LV weight-to-body weight ratio (C: 2.0 ± 0.5 mg/g; AAS: 3.3 ± 0.7 mg/g), LV relative wall thickness (C: 0.19 ± 0.02; AAS; 0.34 ± 0.10), and LV fractional shortening (C: 54 ± 5%; AAS: 70 ± 8%) were increased in the group AAS (p<0.05). Echocardiographic analysis also indicated a significant association (r=0.74; p<0.001) between percent fractional shortening and LV relative wall thickness. The performance of AAS isolated muscle revealed that active tension (C: 6.6 ± 1.7 g/mm 2; AAS: 6.5 ± 1.5 g/mm 2) and maximum rate of tension development (C: 69 ± 21 g/mm 2/s; AAS: 69 ± 18 g/mm 2) were not significantly different from group C (p>0.05). In conclusion: 1) Compensated pressure-overload myocardial hypertrophy is associated with preserved myocardial function and increased ventricular performance; 2) The improved LV function might be due to the ventricular remodeling characterized by an increased relative wall thickness. Copyright © 2002 By PJD Publications Limited.
Keywords: Aortic stenosis; Cardiac function; Echocardiography; Left ventricular hypertrophy; Papillary muscle; animal experiment; animal model; animal tissue; aorta stenosis; body weight; controlled study; echocardiography; heart left ventricle ejection fraction; heart left ventricle hypertrophy; heart papillary muscle; heart rate; heart weight; male; muscle isometric contraction; nonhuman; rat; spontaneously hypertensive rat; statistical analysis